Agonistic security: Transcending (de/re)constructive divides in critical security studies. (August 2021) - Tulumello, Simone
This article aims to contribute toward transcending the dichotomy between deconstruction and reconstruction in critical security studies. In the first part, I review dominant (Western/liberal) logics of security and the main strands of critical security studies to argue that there is a need to overcome the liberal framework of the balance between rights and freedom, with its inherent imbrication with the fantasy of absolute security; and, contra the ultimate conclusions of deconstructive critique, at the same time to take the desire for security seriously. By advocating in favor of embracing the tensions that surface at the intersection of these two conclusions, I then move to my reconstructive endeavor. I set out a meta-theory – that of agonistic security – that is both analytical and normative in nature and inspired by the political theory developed by Mouffe and Laclau. Building on the opposition between antagonism and agonism, I argue that security belongs to the 'political' and that it constitutes a field of struggle for politicization. I then argue for three conceptual shifts that concretely define agonistic security: (i) from an absolute/static to a relational/dynamic understanding of security; (ii) from universalism to pluralism at a world scale; and (iii) from the dominance of individual rights in Western/liberal thinking toward an understanding of security as a collective endeavor. In conclusion, I take a step back and discuss the implications of agonistic security for the role of critique in security studies.